Analisis perilaku nasabah dalam keputusan penggunaan layanan mobile banking - Bintang Kartika; Muhammad Iqbal Fasa (Jurnal Intelek Dan Cendikiawan Nusantara, 2024)
Current technological advances have greatly influenced the development of digital banking which allows banking transactions to be carried out more easily and efficiently. Mobile banking offers many benefits to banks and customers. For banks, this advantage provides a competitive advantage over banks that do not provide similar services, and allows them to reach new customer segments, both individuals and companies, who are taking advantage of mobile phone innovations. Apart from that, mobile banking also helps reduce employee, courier, communication, document and other costs. Mobile banking or m-banking is seen as an important information system service in banking which is able to provide financial information such as balance checks, fund transfers, credit card bill information, and bill payments via devices with wireless internet connections. For customers, it is important to easily access financial information and carry out transactions online without the need to visit the bank. If customers are satisfied with the speed and accuracy received as well as the ease of transactions, then the goal of m-banking services as a value-added banking information system will be achieved.